Effect of Foliar Application of Nutrient Solation [Marval] and Salicylic acid and Their Interaction on Flowering and Chemical Characteristics of Jujube Tree Zizphus mauritiana Lamk. cv. Tayahi - Ameir, Nada A.; Muhammad, Khawla H.; Abdulwahed, Aqeel H. (Journal of Kerbala for Agricultural Sciences, 2018)
The present experiment was carried out in a private orcharal, Al-Hartha north of Basrah during the growing season of 2015. Ten year old jujube trees cv. Tufahi were used. The tree were sprayed with the nutrient solution Marvel at (0, 4 and 8)ml.l-1 and Salicylic acid at (0, 50, 100 and 150)mg.l-1 and their interaction. The trees were sprayed twice with an interval of one month the effect of these treatments on flowering and chemical characteristic studied. The results showed that treatment with the nutrient solution (marvel) caused a significant increase in all flowering characteristic (length of flowering stalk, number flower cluster) and chemical characteristic including N, P, K and Fe leaf content. The results also showed that’s spraying with SA giving 150 mg.l-1 caused a significant increase in flower and chemical characters as for the interaction effect on trees sprayed with 8 ml.l-1 Marvel + 150 mg.L SA recorded the highest studied characteristics.